Visitors' level of awareness on safety instructions at Giant Panda Conservation Centre (GPCC), Zoo Negara, Malaysia - Siew, Kar Man (2016)
People visiting Giant Panda in Zoo Negara Malaysia is getting more after the birth of the panda cub. Hence, in order to well manage the crowd due to the Giant Panda, the management needs to know further about the visitors‟ information, interest and their behaviour. There are several aspects to discover and one of the important aspects is safety. Therefore, this study was mainly to determine the visitors‟ level of awareness on safety instructions in Giant Panda Conservation Centre (GPCC), Zoo Negara. The data for this study was obtained from both primary and secondary data. Primary data were collected from the visitors coming to Giant Panda Conservation Centre (GPCC), Zoo Negara through personal interview and questionnaire. Whereas secondary data was collected from relevant journals, books, website and internet searches. A questionnaire was designed to collect data from visitors to GPCC. Four factors were found significantly influencing the level of awareness on safety instructions at GPCC. Companion to visit GPCC which is not with family, Indian ethnic respondents, Malay ethnic respondents and self-employed occupation were identified as the factors that influencing the level of awareness on safety instructions at GPCC.